SURVEI KEPUASAN MASYARAKAT TERHADAP PELAYANAN PUBLIK KANTOR DESA TATAH LAYAP KECAMATAN TATAH MAKMUR KABUPATEN BANJAR - Ahmad Jazuli; Siti Fatimah (Jurnal Ilmu Ekonomi dan Bisnis, 2019)
Abstract: Public services are very important, both in the form of public goods and public services. Services in the form of public goods can be facilities that support people's lives such as roads, clean water and so on. The higher the quality of service in the form of public goods, the people's lives will be good, meaning that there are no problems that hinder in carrying out daily activities. While services in the form of services are very much needed by the community, such as health and education services and transportation. The services at the Tatah Layap Village Office in the District of Tatah Makmur, Banjar Regency in the category of service quality